Distribution, trends, and drivers of flash droughts in the United Kingdom - Noguera, Iván; Hannaford, Jamie; Tanguy, Maliko (Hydrology and earth system sciences, 2025)
Flash droughts have been the subject of a great deal of scientific attention in the last decade, but the greatest emphasis has been on relatively dry climates. Here, we characterise this type of rapid-onset drought events in a more humid setting, the United Kingdom (UK), for the period 1969–2021. Our results show that flash droughts have affected both the wetter regions of the north-west and the drier regions of the south-east in every season over the last 5 decades. Nevertheless, the spatio-temporal distribution of flash droughts is highly variable in the UK, with important regional and seasonal contrasts. Central and northern regions are generally the most frequently affected by flash droughts in comparison to the south-eastern region. Overall, there are non-significant trends in the frequency of flash droughts in winter, summer, and autumn. However, we found a significant increase in the number of flash droughts recorded in spring. We also analysed the relative contribution of the atmospheric evaporative demand (AED) and precipitation to flash drought development in the UK. Our findings show that flash drought occurrence responds primarily to precipitation variability in all seasons but particularly in winter and autumn. In spring and summer, the AED is important as a secondary driver for triggering flash droughts, especially in the drier regions of the south-east. Furthermore, the trends observed in AED contribution evidence that its relevance is rising significantly in spring, also in the south-eastern UK in summer. The atmospheric and oceanic conditions related to flash drought development were also examined. Remarkable anomalies in sea level pressure and 500 hPa geopotential height associated with the presence of high-pressure systems are noted in all seasons during the development of the main flash droughts affecting the UK. Similarly, flash droughts typically develop under the negative phase of the North Atlantic Oscillation in winter and autumn, while in summer and spring the positive phase is dominant. We also found positive anomalies in sea surface temperature during the development of flash droughts in spring and summer, while mixed anomalies are observed in winter and autumn. This study presents a detailed characterisation of the flash drought phenomenon in the UK, providing useful information for drought assessment and management and a climatology of flash droughts that can be used as a baseline against which future changes in flash drought occurrence can be assessed.